Analysis of Sequences and Molecular Evolution in the Iraqi Date Palm Cultivars (Phoenix dactylifera L.) Propagated by Tissue Culture, Based on ITS1 Region - Hawash, Mohammed M.; Al-Shamma, Laith M.J. (Iraqi Journal of Science, 2025)
The study involved seven Iraqi date palm (Phoenix dactylifera L.) cultivars propagated through tissue culture (TC) and two cultivars propagated by offshoots (Offs). The internal transcribed spacer 1 (ITS1) region of nuclear ribosomal DNA (nrDNA) was used as the marker for investigation. In an effort to institute genetic relations between various date palm cultivars and uncover their molecular evolution, trees were constructed using the ''neighbor-joining''  (NJ) and ''maximum parsimony'' (MP) approaches. The variation in GC content in the ITS1 region was recorded at 52–53%. The data suggests that transitions have a lower frequency compared to transversions in this region, where the overall bias R for transition/transversion has been estimated at 0.751. The aligned sequences of the cultivars were identified to be 637 bp, and the divergence values were observed to range between (0.0000%) and (0.0063%). Out of the nine cultivars, the aligned sequences permitted us to pinpoint eight haplotypes. The outcomes refer to a gradual demographic expansion for an Iraqi date palm population that will arrive at equilibrium after 0.6N generations. The research findings revealed that the Mir alhajj TC cultivar exhibited the highest susceptibility and sensitivity among the examined cultivars when propagated through the tissue culture technique. The primary 2 constituents' multi-variate PCA analysis revealed that PC1 had a variability of 0.9599 among cultivars and an Eigen value of 7.7099, whereas PC2 had a variation of 0.9766 and an Eigen value of 6.7500. Analysis of these ITS1 sequences revealed that they offer adequate variability in characteristics to investigate the relationships among genotypes and explore the evolutionary lineage between the cultivars studied. Moreover, the observed diversity among closely related genotypes provides robust evidence for the efficacy of ITS1 sequences in figuring out relationships and identifying the evolutionary history of those cultivars.